Silver(I)-Catalysed Synthesis of Cuneanes from Cubanes and their Investigation as Isosteres - Smith, Elliot J. (2024)
Bridged or caged polycyclic hydrocarbons with well-defined exit vectors are valuable scaffolds for applications in medicinal chemistry. The development of synthetic methods for accessing new 3D building blocks and saturated isosteres of aromatic rings based on these motifs is a topic of significant current interest in organic chemistry. Cubane has received considerable attention as a saturated phenyl ring bioisostere, but its lesser-strained valence isomer cuneane has been sparsely explored. Here, we report methodology for the regioselective synthesis of both 2,6- and 1,3- substituted cuneanes from cubanes, with the regioselectivity being dependant on both the electronic character of the cubane substituents and the choice of reaction conditions. Preliminary computational studies were undertaken that suggest cuneanes could act as isosteres of trans-1,4-disubstituted cyclohexanes and meta-substituted phenyl rings. Finally, the synthesis of a cuneane-containing analog of the anticancer drug sonidegib was carried out.